Study of the permeability of the plasma membrane of human erythrocytes for DMSO molecules in the presence of PVA of various concentrations - Hvozdiuk, Yana; Kovalenko, Svitlana; Gurina, Tetiana (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):243